Segregation analysis for bacterial leaf blight disease resistance genes in rice ‘MR219’ using SSR marker - Mohd Zuki, Zakiah; Yusop, Mohd Rafii; Ramli, Asfaliza; Yusuff, Oladosu; Latif, Mohammad Abdul; Sijam, Kamaruzaman; Ismail, Mohd Razi; Mohd Sarif, Hamidah (Instituto de Investigaciones Agropecuarias, 2020)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae is one of the major hindrances in rice (Oryza sativa L.) production across the world including Malaysia. Therefore, the development of disease-resistant varieties remains a very economical and effective method of controlling BLB in rice. Based on this background, this study was conducted to analyze segregation pattern of simple-sequence repeat (SSR) markers associated with BLB resistance genes in an F2 bulk population derived from a resistant variety (IRBB60) and a susceptible variety (MR219). Out of 129 simple sequence repeat (SSR) markers screened, 18 distinct polymorphism markers including R-gene based markers were used to screen 345 F2 progenies for resistance to BLB. Among the polymorphic markers, the chi-square analyses showed that 15 SSR markers (i.e. RM13 (xa5), RM21 (Xa21), RM122 (xa5), RM153 (xa5), RM164 (Xa13), RM206 (Xa10), RM5509, RM20B, RM25, RM163, RM169, RM218, RM267, RM276, and RM334) had a segregation ratio of 1:2:1 for a single gene model (df = 2.0, p ≤ 0.05). For phenotypic ratio, the F2 population segregated in ratio 3:1 (R:S) for resistant and susceptible plants, respectively. This indicated that resistance to BLB caused by pathotype X. oryzae pv. oryzae (Xoo) in the ‘MR219’ × ‘IRBB60’ F2 population is controlled by single dominant genes. The result presented in this study will help breeders to further breeding research in rice by enabling selection based on the genotype rather than on the phenotype. Similarly, the markers reported in this study will serve as a valuable tool for marker-aided selection for BLB resistance gene.